Analisis Sikap Petani Padi Terhadap Atribut Pupuk Subsidi Di Kabupaten Jember - Pranowo, Igit Ginanjar; Zainuddin, Ahmad (Department of Agricultural Social Economics, Faculty of Agriculture, Brawijaya University, 2024)
Development in the agricultural sector in the context of supporting national food security is the main concern of the government. In this case the government has issued a policy to strengthen food security and anticipate extreme climate conditions that could disrupt national food production, namely by providing direct assistance policies in the form of distribution of subsidized fertilizers through farmer groups. The agricultural policy is contained in regulations and the Decree of the Minister of Agriculture No. 106/Kpts/SR.130/2/2004 regarding subsidized fertilizer policies. The policy states that the reason for providing subsidized fertilizers is in the context of realizing a national food security program through increasing production of agricultural commodities. Farmers immediately respond either in purchasing or using subsidized fertilizers directly or indirectly. Based on this, this study aims to analyze what factors influence rice farmers' decisions to buy subsidized fertilizers in Jember Regency. Location determination using purposive sampling method, and the data used is primary data with interview techniques using a questionnaire. The analytical method used is by using Logistic Regression Analysis. The sampling method used is multistage sampling with certain considerations, namely incidental sampling. The results of logistic regression analysis showed that the independent variables had an influence on the dependent variable (the decision to buy subsidized fertilizer) in this study, namely income (X3), price of subsidized urea fertilizer (X6), and place of purchase (D9). While the variables Age (X1), Education (X2), Number of Family Members (X4), Land Area (X5), Price of Non-Subsidized Urea Fertilizer (X7), Access to Information (D8), Fertilizer Availability (D10) have no effect on the variable dependent (decision to buy subsidized fertilizer). The results of the analysis also show that the Nagelkerke R Square value is 0.533 or it can mean that the variability of the dependent variable can be explained by the variability of the independent variables of 53.3% and the remaining 46.7% is explained by the diversity of other variables outside the model. The conclusions of the research results are: 1) Factors that partially have a significant influence on farmers' decisions in buying subsidized fertilizer in Jember Regency based on the Wald test with a confidence level of 90% are income, price of subsidized urea fertilizer and place of purchase. Meanwhile, the factors that partially have an insignificant effect based on the Wald test are age, education, number of family members, land area, price of non-subsidized urea fertilizer, access to information and availability of fertilizer.Keywords: Attitude, Rice Farmer, Logistic Regression Analysis